Researching Sources of the Social Pedagogics Development Problem as a Science in Ukraine - Shtefan, Lyudmyla (Pedagogical Discourse, 2013)
The article gives analysis of the dissertations, text-books, the national and foreign researchers’ works dedicated to the problems of the development of the social pedagogic as science in Ukraine. Besides, there are analyzed the documents and the materials of the Central State History Archive in Kyiv, the Central State Archive of the Ukrainian Authorities and Management, the State Archive in Kharkiv Region, the Department of Manuscripts at the V.I.Vernadsky Scientific Library of the National Academy of Science in Ukraine, the Russian State Library, the issues of the rare books and Ukrainian studies departments at the V.Vernadsky Central Scientific Library of the Academy of Science of Ukraine, Scientific and Reference Literature Library of the Central State History Archive in Kyiv, the V.Korolenko state scientific library in Kharkiv, the V.N.Karazin Kharkiv National University the museums of the V.H.Korolenka and A.Makarenka Kharkiv regional secondary boarding school for the blind schoolchildren in Kuriazh.